Cho \(A = {x^3} + {x^2} - 2...

Câu hỏi: Cho \(A = {x^3} + {x^2} - 2x + 1\) và \(B = x - 1\) Tìm phần dư R và thương Q trong phép chia A cho B  rồi viết A dưới dạng A = B.Q +R ta được kết quả nào sau đây?

A. \({x^3} + {x^2} - 2x + 1 = \left( {x - 1} \right)\left( {{x^2} + x} \right) + 3\)

B. \({x^3} + {x^2} - 2x + 1 = \left( {x - 1} \right)\left( {{x^2} + x} \right) + 1\)

C. \({x^3} + {x^2} - 2x + 1 = \left( {x - 1} \right)\left( {{x^2} + 2x} \right) + 3\)

D. \({x^3} + {x^2} - 2x + 1 = \left( {x - 1} \right)\left( {{x^2} + 2x} \right) + 1\)